Comprehensive Review on Withania coagulans Dunal: Unveiling Pharmacognosy, Phytochemistry and Pharmacological Potentials - Sinoriya, Pooja; Kaushik, Rahul; Sinoria, Arti; Gaur, Praveen Kumar (Pharmacognosy Reviews)
Background: The Solanaceae family plant Withania coagulans (Stocks) Dunal is also known by the names vegetable rennet, paneer doda, paneer ka phool and rishyagandha. It is widely used in traditional medicines in countries like Pakistan, Iran, Afghanistan and East-West India. Since ancient times, herbs have been effective such as sedative, nervous system, depressant, hepatoprotective and treatment for various illnesses like diabetes, heart problem, cancer and asthma. The smoke from the plant is inhaled to ease toothaches and the twigs are chewed to clean teeth. This overview study analyses scientific and therapeutic prospects for further research on Withania coagulans and offers extensive information on the morphological, biochemical and pharmacological effects. Materials and Methods: ScienceDirect, Pub Med, Google Scholar, Scopus, or Research Gate are the scientific research databases has been utilized for gathering their information for the study of Withania coagulans Dunal. The pharmacological, pharmacognostical and phytochemical properties of Withania coagulans are summarized in this article. Results: Various parts and its pharmacological properties have been reported in Withania coagulans including anti-hyperglycemic, anti-inflammatory, anti-fungal, anti-bacterial, anti-asthmatic, hepatoprotective, immunosuppressive, sedative, diuretic and depressant medication. In additionally bioactive compounds has been isolated like withanolide, fatty acid, aromatic ester, 1-methyl-octadecanoic acid, hexanoic acid, n-hexadecenoic acid, Vitamin E. Conclusion: A comprehensive survey literatures concerning the morphological, microscopy, traditional uses, phytochemical and pharmacological effects for a wide variety of herbal extract presented in this review. Since numerous aspects plant extract have not yet been explored, some traditional uses still require validation in order to discover the unexplored opportunities of this plant.
Keywords: Bioactive compounds; Ethnobotanical aspects; Natural products; Ethnopharmacology